Left ventricular mass indexing in infants, children, and adolescents: a simplified approach for the identification of left ventricular hypertrophy in clinical practice - Chinali, Marcello; Emma, Francesco; Esposito, Claudia; Rinelli, Gabriele; Franceschini, Alessio; Doyon, Anke; Raimondi, Francesca; Pongiglione, Giacomo; Schaefer, Franz; Matteucci, Maria Chiara (The journal of pediatrics, 2016)
Objective To determine a simplified method to identify presence of left ventricular hypertrophy (LVH) in pediatric populations because the relationship between heart growth and body growth in children has made indexing difficult for younger ages. Study design Healthy children (n = 400; 52% boys, 0-18 years of age) from 2 different European hospitals were studied to derive a simplified formula. Left ventricular mass (LVM) was calculated according to the Devereux formula. The derived approach to index LVM was tested on a validation cohort of 130 healthy children from a different hospital center. Results There was a strong nonlinear correlation between height and LVM. LVM was best related to height to a power of 2.16 with a correction factor of 0.09.
Published online: December 06, 2015
Gesehen am 30.04.2020